Reasons affecting the uptake of reproductive genetic carrier screening among nonpregnant reproductive‐aged women in Flanders (Belgium). Issue 5 (6th April 2022) - Van Steijvoort, Eva; Demuynck, Remke; Peeters, Hilde; Vandecruys, Hilde; Verguts, Jasper; Peeraer, Karen; Matthijs, Gert; Borry, Pascal
Abstract: Reproductive genetic carrier screening (RGCS) allows to identify couples who have an increased likelihood of conceiving a child affected with an autosomal recessive or X‐linked monogenic condition. Multiple studies have reported on a wide and fragmented set of reasons to accept or decline RGCS. Only a few studies have been performed to assess the uptake of RGCS. Nonpregnant women visiting their gynecologist were invited to complete a questionnaire assessing perceived susceptibility, the acceptability of offering RGCS, attitudes, the intention to participate in RGCS, reasons to accept or decline RGCS, and sociodemographic characteristics. Women who showed the intention to have RGCS were asked to consider a free RGCS offer. Most women ( n  = 127) were between 25 and 34 years old (60%), in a relationship (91%), and wanted to have children (65%). Study participants had positive attitudes towards RGCS and the intention to consider RGCS in the future. Reasons to accept RGCS were being able to share genetic information with children or relatives ( n  = 104/127, 82%), to prevent the birth of a child affected with a hereditary condition ( n  = 103/127, 81%), and/or to know the chance of conceiving a child with a hereditary condition ( n  = 102/127, 80%). Reasons for declining RGCS were the possible concerns that could arise when receiving test results ( n  = 27/127, 21%), having no family history of hereditary disorders ( n  = 19/127, 15%), and not wanting to take action based on test results ( n  = 13/127, 10%). Among test intenders that met the inclusion criteria, 53% decided to participate in RGCS together with their male reproductive partner. More in‐depth research on the decision‐making process behind the choice to accept or decline an RGCS offer would be highly valuable to make sure couples are making informed reproductive choices.